Assessment of sustainable urbanization in Ukrainian regions - Venhryn, Darya (Human Geography Journal, 2024)
The high level of urbanization worldwide and in Ukraine significantly impacts the environmental, economic, and social spheres, creating additional challenges for their balanced development. The rapid growth of this process necessitates the introduction of new research approaches. One such approach is the indicator of sustainable urbanization. It encompasses environmental, social, and economic sustainability, including all types of settlements – from rural areas to megacities – and facilitates the formation of interconnections at national and global levels. Understanding the principles of sustainable urbanization is a crucial tool for effective regional management, as it allows for the analysis of current processes, identification of their strengths and weaknesses, faster improvement of the population’s quality of life, ensuring ecological balance and reducing the negative impact on the environment. This study evaluates the level of sustainable urbanization in six regions of Ukraine with the largest administrative centers (Kharkiv, Kyiv, Dnipropetrovsk, Odesa, Lviv, and Vinnytsia regions). The analysis was based on the calculation of the urbanization level and the assessment of sustainable regional development, using indicators highlighted in regional development strategies. These indicators were grouped by three categories: economic, social, and environmental. The research findings were presented on a coordinate plane, enabling the identification of four scenarios of urbanization processes: sustainable counter-urbanization, unviable counter-urbanization, unsustainable urbanization, and sustainable urbanization. The most effective scenario is sustainable urbanization, which supports improved quality of life, preserves ecological balance, and minimizes negative environmental impact. The study highlights the importance of a well-grounded approach to analyzing urbanization processes and developing new strategies for sustainable development of cities and regions. The results provide local authorities with the tools to assess the compliance of urbanization processes with sustainable development goals, guiding them in the right direction.